The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1038/ncomms7445
|View full text |Cite
|
Sign up to set email alerts
|

Total synthesis of clostrubin

Abstract: Clostrubin is a potent antibiotic against methicillin- and vancomycin-resistant bacteria that was isolated from a strictly anaerobic bacterium Clostridium beijerinckii in 2014. This polyphenol possesses a fully substituted arene moiety on its pentacyclic scaffold, which poses a considerable challenge for chemical synthesis. Here we report the first total synthesis of clostrubin in nine steps (the longest linear sequence). A desymmetrization strategy is exploited based on the inherent structural feature of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
42
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 77 publications
2
42
0
1
Order By: Relevance
“…Furthermore, the surface carrier dynamics are independent of excitation density ( fig. S6), suggesting that the fast decay kinetics are not affected by bulk recombination (21). We fit a diffusion model to the kinetic trace with the ambipolar diffusion coefficient and the surface recombination velocity (SRV) as best-fit parameters with values of 0.5 cm 2 s -1 and 500 cm s -1 , respectively.…”
Section: R ðℏWþºdf•aðfþ ð 1þmentioning
confidence: 99%
“…Furthermore, the surface carrier dynamics are independent of excitation density ( fig. S6), suggesting that the fast decay kinetics are not affected by bulk recombination (21). We fit a diffusion model to the kinetic trace with the ambipolar diffusion coefficient and the surface recombination velocity (SRV) as best-fit parameters with values of 0.5 cm 2 s -1 and 500 cm s -1 , respectively.…”
Section: R ðℏWþºdf•aðfþ ð 1þmentioning
confidence: 99%
“…1C). Although various molecular and macroscopic constructs implement the basic principles of strain stiffening (6)(7)(8)(9)(10)(11), none replicate tissue's deformation response completely and precisely. For example, various silicone rubbers, such as Ecoflex and Dragon Skin, which are widely used in orthotics and cinematography (17), have skinlike softness but lack the strain-stiffening characteristics of skin (Fig.…”
mentioning
confidence: 99%
“…GRK2 and GRK6 promote the phosphorylation of β-arrestin and then recruit SRC kinase to the GPCR/β-arrestin complex. 8 Consistently, the authors found that TGR5-GRK-βarrestin mediated SRC activation and thereafter promoted the antiviral response. Taken together, BAs facilitate innate antiviral response via TGR5-GRK-β-arrestin-SRC activation.…”
mentioning
confidence: 73%